(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Taxes are an essential axis in the economy as the most effective and effective economic tool in any country (economy). Expanding the scope of taxation without adequate study has produced a dangerous result with a negative impact that is almost apparent, namely (tax evasion), which stands as a barrier preventing the state from reaching Therefore, the research sought to study strategic tax planning and its importance in reducing tax evasion, and the research aims from that to prove the importance of adopting strategic planning in the field of taxes according to modern and effective scientific foundations to reduce tax evasion to enhance the achievement of tax evasion. The financing objective is in addition to the other objectives, and the research problem is summarized in the extent to which the tax system follows the strategic planning of taxes in order to achieve the tax objectives and the effectiveness of this planning (strategic planning) in reducing tax evasion, and therefore the research sample was taken to include (specialists, workers, and taxpayers) and it was The sample is 105 individuals, and accordingly the study came out with results, the most important of which are; The importance of strategic planning in relation to reducing tax evasion, the existence of a weak correlation that is close to being of medium strength with a statistical significance between strategic planning and its importance in reducing tax evasion reflects the lack of interest of the sample in question in strategic planning, there was a significant statistically significant effect between strategic planning For taxes and the reduction of tax evasion, the decrease in the relative importance of taxes in general for the state, especially in the financing aspect, if, during the past 15 years, its contribution to the state’s general budget did not reach 4%, which is less than a shy percentage. The increase in tax revenues is an unreal increase, as it is As a result of the increase in government spending and the increase in inflation rates.